2022
DOI: 10.1093/noajnl/vdab191
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA copy number as a prognostic marker is age-dependent in adult glioblastoma

Abstract: Background Glioblastoma (GBM) is the most common and aggressive form of glioma. GBM frequently displays chromosome (chr) 7 gain, chr 10 loss and/or EGFR amplification (chr7+/chr10-/EGFRamp). Overall survival (OS) is 15 months after treatment. In young adults, IDH1/2 mutations are associated with longer survival. In children, histone H3 mutations portend a dismal prognosis. Novel reliable prognostic markers are needed in GBM. We assessed the prognostic value of mitochondrial DNA (mtDNA) copy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…This observation aligns with previous studies that highlighted the correlation between increased mtDNA copy numbers and improved overall survival in GBM patients. 14 , 15 Additionally, our observations revealed that elevated mtDNA content displayed a favorable prognosis in high-grade tumor patients. A prior study similarly emphasized the significance of the increased mtDNA content in the survival of high-grade glioma patients.…”
Section: Discussionsupporting
confidence: 55%
“…This observation aligns with previous studies that highlighted the correlation between increased mtDNA copy numbers and improved overall survival in GBM patients. 14 , 15 Additionally, our observations revealed that elevated mtDNA content displayed a favorable prognosis in high-grade tumor patients. A prior study similarly emphasized the significance of the increased mtDNA content in the survival of high-grade glioma patients.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, mtDNA depletion was associated with cancer progression to a more malignant phenotype with adverse prognosis in glioblastoma patients [ 30 , 35 ]. mtDNA copy number has been a novel prognostic biomarker in GBM [ 36 , 37 ]. Additionally, we observed in the present study that rotenone-induced mitochondrial dysfunction promoted TMZ resistance in glioblastoma cells and that the susceptibility to TMZ treatment was increased with the prolongation of rotenone treatment ( Figure S9a ).…”
Section: Discussionmentioning
confidence: 99%
“…diagnozy [38]. Mutacje IDH1/IDH2 determinują zatem lepsze rokowanie u pacjentów ze zdiagnozowanym glejakiem.…”
Section: Mutacje W Obrębie Idh1/idh2unclassified